Current status of UK radiology trainee experience in post-mortem imaging: A questionnaire-based survey. (June 2017) - Elliott, Claire L.; Arthurs, Owen J.; Young, Jane
Highlights: UK radiology trainees currently lack experience in post-mortem imaging. Radiology trainees desire more exposure to post-mortem imaging during training. Dedicated courses and lectures are needed to ensure training needs are met.